1980
DOI: 10.1002/jcp.1041030118
|View full text |Cite
|
Sign up to set email alerts
|

The stimulation by epidermal growth factor (Urogastrone) of the growth of neonatal rat hepatocytes in primary tissue culture and its modulation by serum and associated pancreatic hormones

Abstract: Epidermal growth factor (EGF) added in a single dose (between 10(-16) and 1.7 X 10(-9)M) to neonatal rat hepatocytes in primary culture with subsequent incubation for 12 and 24 hours in Eagle's MEM fortified with 10% (v/v) FBS stimulated their entry into S and M phases, as shown by (3H)thymidine labeling and autoradiography and by a 4-hour exposure to colchicine (0.1 mM). Growth stimulation by EGF was detectable after 4 hours, peaking between 12 and 16 hours, and thereafter declining in intensity. Rat hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…The principal intent of this report is to document the effects of ethanol directly on fetal cells and on the growth factor interactions required for replication of these cells. These studies indicate that (a) exposure to moderate concentrations of ethanol blocks EGF-dependent replication of rat fetal hepa- (8,28). Our data confirm this and further show that exposure to ethanol blocks this growth.…”
Section: Discussionsupporting
confidence: 88%
“…The principal intent of this report is to document the effects of ethanol directly on fetal cells and on the growth factor interactions required for replication of these cells. These studies indicate that (a) exposure to moderate concentrations of ethanol blocks EGF-dependent replication of rat fetal hepa- (8,28). Our data confirm this and further show that exposure to ethanol blocks this growth.…”
Section: Discussionsupporting
confidence: 88%
“…The present results demonstrate a wide difference in the replicative activity of suckling versus adult rat hepatocytes in response to EGF, insulin, and glucagon A number of studies have been reported on the replicative activity of hepatocytes from 4-day-old rats, in response to these hormonal factors (Andreis and Armato, 1981;Draghi et al, 1980). However in those studies, hepatocytes represented only 40% of the isolated liver cell preparations and were stimulated after 4 days of culture in the presence of serum; such culture conditions are very different from those used to study the hormone response of adult rat hepatocytes (e.g., Laishes and Williams, 1976a;McGowan et al, 1981;Michalopoulos et al, 1982).…”
Section: Discussionmentioning
confidence: 78%
“…Although EGF appears to have a growth-promoting effect on hepatocytes (17) and hepatocytes have been shown to contain saturable EGF receptors (18), a high-capacity uptake system with the ability to translocate immunoactive EGF across the hepatocyte has, to the best of our knowledge, not been demonstrated previously.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the growth-promoting capabilities of EGF are not expressed in normal liver because liver cells divide at an exceedingly slow rate. However, EGF treatment has been shown under special circumstances to induce hepatic hypertrophy and hyperplasia in vivo (16), to induce DNA synthesis in rat hepatocytes in vitro (15,17), and to increase neonatal hepatocyte numbers in vitro (17). Based on these studies as well as those of Earp (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation